Measuring and Rigidity Moduli of GFRP Experimentally - Youssef A. Awad; Ahmed M. El-Fiky; Hosam M. Hegazy; Mahmoud G. Hasan; Ibrahim A. Yousef; Ahmed M. Ebid; Mohamed A. Khalaf (Civil Engineering Journal, 2023)
Although GFRP poles are widely accepted today due to their low cost and weight and high electrical and corrosion resistance, they suffer large deformations due to the low elastic and rigidity moduli (E & G) values of the GFRP. Accordingly, it is essential to accurately measure these values to estimate the actual deformation of the pole. This study presented a procedure to measure (E & G) values using three different tests on three sample sizes: full, scale pole, conic sample, and ad coupon sample, instead of using the manufacturer values as usual. This study is also concerned with the shear modulus value and when it can be neglected as usual in other traditional materials. The GRG optimization technique was used to analyze the results and determine the optimum values for (E & G) considering the results of the three tests. The results showed that the values of (E & G) are greatly affected by the sample’s size and shape, the slenderness ratio of the sample (L/r), and the shear deformation contribution. The critical slenderness ratio (L/r), corresponding to a shear deformation contribution of 10%, was determined for each test. This value is recommended as the upper boundary for any test that measures the (E & G) values. Testing several samples with different (L/r) values is also recommended to enhance accuracy. This study was concerned with determining the optimum values of elastic and rigidity moduli for GRFP poles compared to the manufacturer’s conservative values. The results indicated that the shear modulus can be neglected and the importance of the scale effect on the results of flexure and shear modulus. Doi: 10.28991/CEJ-2023-09-08-07 Full Text: PDF